Al ritmo latino - Sillanpää, Jari; Puerto, Carlos D'l; Nykänen, Anssi; Espinosa, Pepe; Lanu, Juha; Gonzalez, Oldrich; Mäkinen, Mikko; Terry Cabrera, Yoel; Curbelo, Harlem; Siitonen, Hanna-Riikka; Tuhkala, Marika; Tapio, Nina (Bridgehead Productions, 2008)
18 kappaletta.
Keywords: Sillanpää, Jari, : 1965- : albumit